2023
DOI: 10.1167/tvst.12.2.27
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Single-Gene Worldwide Carrier Frequency and Genetic Prevalence Analysis of CYP4V2 as the Cause of Bietti Crystalline Dystrophy

Abstract: Purpose Bietti crystalline dystrophy (BCD) is a rare monogenic autosomal recessive (AR) chorioretinal degenerative disease caused by biallelic mutations in CYP4V2 . The aim of the current study was to perform an in-depth calculation of worldwide carrier frequency and genetic prevalence of BCD using gnomAD data and comprehensive literature CYP4V2 analysis. Methods CYP4V2 gnomAD data and reported mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 13 However, prevalence of BCD is estimated to be around 1:116,000 according to a recent study. 15 In a group of 207 consecutive retinitis pigmentosa (RP) patients, 4 BCD cases were identified, and BCD prevalence was estimated to be 2.5% of all RP patients. 16 Matafsi et al 16 revealed that BCD was diagnosed in 3% of non-syndromic RP cases and the equivalent frequency increased to 10% when autosomal recessive RP was considered.…”
Section: Epidemiologymentioning
confidence: 99%
“… 13 However, prevalence of BCD is estimated to be around 1:116,000 according to a recent study. 15 In a group of 207 consecutive retinitis pigmentosa (RP) patients, 4 BCD cases were identified, and BCD prevalence was estimated to be 2.5% of all RP patients. 16 Matafsi et al 16 revealed that BCD was diagnosed in 3% of non-syndromic RP cases and the equivalent frequency increased to 10% when autosomal recessive RP was considered.…”
Section: Epidemiologymentioning
confidence: 99%